Цільові функціонали регіональної стратегії управління забезпеченням енергоефективності промисловості - Микитенко, В.В.; Худолей, В.Ю. (Економіка природокористування і охорони довкілля, 2013)
Розкрито зміст і регулятори алокаційної стратегії управління забезпеченням енергоефективності функціонування РПК. Ідентифіковано критерії оцінювання її результативності та обмеження, які існують в Україні. Розроблено замкнений цикл формування стратегії, адекватної реальним виробничо-господарським і соціально-економічним процесам і національній економіці, що здійснено за п’ятнадцятьма етапами реалізації економетричних, управлінських і системно-універсальних процедур. Maintenance of rational distribution and redistribution of functional strategy of management is exposed by providing of power efficiency of functioning of regional industrial complexes. Criteria are identified estimations of her effectiveness and limitation, which exist in Ukraine. The reserved cycle of forming is worked out by adequate to the real productive and economic, socio-economic terms of functioning of national economy, that it is formalized after fifteen implementation of model decisions, administrative and system-universal procedures phases. Optimization composition of methods is formed, methods and applied tool of adjusting and adjustment of activity on the increase of level of power efficiency of functioning of regional economy and her industry. Groups over of measures and regulators, after that providing of effectiveness of strategic management of functioning real to the sector of regional economy power efficiency becomes probabilistic in case of formalization within the limits of the state of ten cascades to that the modern regional to trade are incorporated complex of Ukraine, are brought.